Circular Bioeconomy and Climate Governance in the Andean Region: Foundations for an Andean Green Deal - Fairlie Reinoso, Alan (2026)
This article examines the relevance of emerging sustainable development paradigms in the Andean region, focusing on bioeconomy, circular economy, biotrade, and, in an integrated manner, the green circular bioeconomy. Using a qualitative and comparative approach, the study analyzes the European Green Deal as a reference framework to assess the institutional, productive, and governance capacities of the Andean Community (CAN) in addressing climate change challenges. The findings indicate that, while each paradigm offers valuable contributions, their isolated application is insufficient to address the complexity of environmental, social, and structural challenges faced by the region. In this context, the green circular bioeconomy emerges as the most coherent approach, as it integrates the sustainable valorization of biodiversity, circularity principles, technological innovation, and explicit objectives related to social inclusion and climate resilience. The analysis also highlights regional integration as a key enabling factor for policy coordination, regulatory harmonization, and the mobilization of green finance. Based on these findings, the paper proposes the development of an Andean Green Deal as a regionally adapted institutional framework aimed at fostering a sustainable, inclusive, and long-term productive transition.